Bildungschancen verbessern: Familien unterstützen - Christina Anger; Axel Plünnecke (Wirtschaftsdienst, 2023)
– The deteriorating competencies of pupils in recent years and the increasing inequality of educational opportunities threaten to re-duce the supply of skilled labour and innovative strength in Germany. The diminishing educational opportunities begin with the fact that parents from educationally disadvantaged households are less able to support their children by reading to them. Children from educationally disadvan-taged households attend early childhood education less often; their parents have greater difficulty finding a place in a day-care centre, have less contact with teachers at schools and are often unable to assist with homework. There are also disadvantages in the choice of educational paths and professions. In order to increase educational equity, parents in particular should receive more language support in early childhood education; all-day facilities should be expanded (as well as the quality in the direction of family centres), more multi-professional staff could be available at schools to support teachers and parents, and STEM subjects and vocational orientation at schools could be strengthened to help improve equal opportunities and better utilise the potential of children from educationally disadvantaged households for securing skilled labour.
Keywords: I24; I28; 330; Bildungswesen; Bildungspolitik; Kinderbetreuung; Eltern; Deutschland; Bildungswesen; Bildungspolitik; Kinderbetreuung; Eltern; Deutschland